The Impact of Interest Rate Changes on Unemployment in Developing Economies: A Time-Series Analysis (2000–2025) - Jigme Chozang (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study examines the impact of interest rate changes on unemployment in developing economies using a time-series framework covering the period 2000–2025. Drawing on official international macroeconomic data and prior empirical research, the analysis explores long-run and short-run relationships between monetary policy and labor market outcomes. The findings indicate that interest rate adjustments significantly influence unemployment persistence, with tightening cycles consistently associated with higher and more durable unemployment levels. Structural factors, including sectoral composition, demographic transitions, and financial market depth, condition the strength of this relationship and generate heterogeneous employment responses across economies. Institutional characteristics such as labor market regulations, policy credibility, and coordination with fiscal measures further mediate how interest rate signals are transmitted to employment outcomes. The study also highlights the role of global financial integration in amplifying external monetary shocks and constraining domestic policy autonomy. Overall, the results suggest that interest rate policy in developing economies has enduring employment consequences that extend beyond cyclical fluctuations. Effective labor market stabilization therefore requires complementary structural reforms and coherent macroeconomic coordination alongside conventional monetary interventions.